2011
DOI: 10.1037/a0022677
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in neuropsychological performance and social functioning in schizophrenia and bipolar disorder.

Abstract: This study is the first to find neurocognitive sex differences for bipolar disorder and replicated previous findings for schizophrenia. The data did not support the hypothesis that sex is a moderator between neurocognition and social functioning. Clinical implications include the use of different cognitive remediation strategies based on sex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
51
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 70 publications
9
51
1
1
Order By: Relevance
“…Many studies have shown that women with schizophrenia perform better than men with schizophrenia in the domain of verbal learning and memory [3,11,22,27,32,45,65,72], which is in line with findings in healthy controls (HC). In other cognitive domains, however, results have been largely inconsistent.…”
Section: Introductionsupporting
confidence: 79%
“…Many studies have shown that women with schizophrenia perform better than men with schizophrenia in the domain of verbal learning and memory [3,11,22,27,32,45,65,72], which is in line with findings in healthy controls (HC). In other cognitive domains, however, results have been largely inconsistent.…”
Section: Introductionsupporting
confidence: 79%
“…Predictably, both clinical groups performed worse than controls on most cognitive tests. In addition, men with schizophrenia performed disproportionally worse relative to their female counterparts on the CVLT, Color-Word Interference, and Interference/Switching tests [162]. In a similar study, Han and colleagues (2012) [163] The patients were overall impaired on the immediate and delayed memory, language, as well as a total score on the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS), which in turn showed moderate inverse correlation with symptom severity, illness duration and antipsychotic dose.…”
Section: Greater Deficit In Men Than In Women With Schizophreniamentioning
confidence: 91%
“…Again, sexual dimorphism in verbal abilities (phonological and semantic fluency) was preserved in SPs (Gogos et al, 2010;Halari et al, 2006) as well as those in word memory in mixed and remitted SP subgroups (Gruzelier et al, 1999) and verbal episodic memory, processing speed and set-shifting efficacy when attention and executive function was measured in the Trail Making Test (Torniainen et al, 2011). Significantly better cognitive performance (verbal memory, speed of processing, and executive function) in females has been also preserved in SPs, in association with higher social functioning compared to male SPs (Vaskinn et al, 2011). Emotional processing assessed by the Penn Emotion Recognition Test was also found to be enhanced in SP and HC females compared with males (Calkins et al, 2013).…”
Section: Sex Differences Shared Between Patients With Schizophrenia Amentioning
confidence: 94%
“…Another study reported impaired facial emotion recognition in SPs with an over-perception of neutral faces as angry in males and as sad in females (Weiss et al, 2007). Deficits in attention (Goldstein et al, 1998;Zhang et al, 2012a), verbal memory (Goldstein et al, 1998;Vaskinn et al, 2011), cognitive flexibility (Vaskinn et al, 2011), language, executive function (Goldstein et al, 1998), mental rotation performances (Jimenez et al, 2009), working memory (Malaspina et al, 2012b, immediate and delayed memory and RBANS total score (Zhang et al, 2012a) were also observed specifically in male SP groups but not in female SP or HC groups.…”
Section: Sex Differences Specific To Patients With Schizophreniamentioning
confidence: 98%